Spontaneous Regression of Pulmonary Nodules Presenting as Epstein-Barr Virus-related Atypical Infectious Mononucleosis. Issue 5 (July 2016) - Shinozuka, Jun; Awaguni, Hitoshi; Tanaka, Shin-ichiro; Makino, Shigeru; Maruyama, Rikken; Inaba, Tohru; Imashuku, Shinsaku
Abstract : Background: Pulmonary nodules associated with Epstein-Barr virus (EBV)-related atypical infectious mononucleosis have rarely been described. Observations: A 12-year-old Japanese boy, upon admission, revealed multiple small round nodules (a total of 7 nodules in 4 to 8 mm size) in the lungs on computed tomography. The hemorrhagic pharyngeal tonsils with hot signals on 18F-fluorodeoxyglucose-positron emission tomography-computed tomography were biopsied revealing the presence of EBV-encoded small nuclear RNA (EBER)-positive cells; however, no lymphoma was noted. The patient was diagnosed as having atypical EBV-infectious mononucleosis associated with primary EBV infection. Pulmonary nodules markedly reduced in numbers and sizes spontaneously over a 2-year period. Conclusions: Differential diagnosis of pulmonary nodules in childhood should include atypical EBV infection.